Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T12:39:45+01:00
A)
x-0,1x=y+3
y+0,1y=x-6

0,9x=y+3
1,1y=x+6

-y=3-0,9x
-x=6-1,1y

y=-3+0,9x
x=-6+1,1y

y=-3+0,9x
x=-6+1,1(-3+0,9x)

y=-3+0,9x
x=-6-3,3+9,9x

y=-3+0,9x
x-9,9x=-9,3

y=-3+0,9x
-8,9x=-2,1

y=-3+0,9x
x=0,23

y=-3+0,9(0,23)
x=0,23

y=-3+0,20
x=0,23

y=-2,8
x=0,23


b)
x=0,2y
x-0,2x=y-21

x=0,2y
0,2y-0,2(0,2y)=y-21

x=0,2y
0,2y-0,04y=y-21

x=0,2y
0,16y-y=-21

x=0,2y
-0,84y=-21

x=0,2y
y=1/4

x=2/10(1/4)
y=1/4

x=1/20
y=1/4

c)
x=y-0,1y
y-2=0,9x

x=0,9y
y=0,9x+2

x=0,9(0,9x+2)
y=0,9x+2

x=0,81x+1,8
y=0,9x+2

x-0,81x=1,8
y=0,9x+2

0,19x=1,8
y=0,9x+2

x=9,47
y=0,9(9,47)+2

x=9,47
y=8,52+2

x=9,47
y=10,52